1986
DOI: 10.1007/bf00181241
|View full text |Cite
|
Sign up to set email alerts
|

Reversal by alpha-2 agonists of diazepam withdrawal hyperactivity in rats

Abstract: Rats were made diazepam dependent by chronic treatment with daily injections of the drug, 20 mg/kg, IP, for 3 weeks. On abrupt termination of the drug, the animals showed withdrawal hyperactivity which was indicated by increased horizontal locomotion and vertical activity, and diarrhoea. The peak effect was seen 3 days after the withdrawal of diazepam. Effects of various alpha 2 agonists, clonidine, guanfacine and B-HT 920, were studied on the diazepam withdrawal phenomena. Clonidine (100 micrograms/kg, IP) gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

1987
1987
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(7 citation statements)
references
References 22 publications
(27 reference statements)
2
5
0
Order By: Relevance
“…The slow time course of withdrawal reaction may be explained in terms of slow elimination of an accumulated active metabolite of parent drug (N-desmethyldiazepam) resulting in the gradual loss of pharmacological activity (Ryan and Boisse 1983). Similar results were seen by Kunchandy and Kulkarni (1986).…”
Section: Discussionsupporting
confidence: 93%
“…The slow time course of withdrawal reaction may be explained in terms of slow elimination of an accumulated active metabolite of parent drug (N-desmethyldiazepam) resulting in the gradual loss of pharmacological activity (Ryan and Boisse 1983). Similar results were seen by Kunchandy and Kulkarni (1986).…”
Section: Discussionsupporting
confidence: 93%
“…1984;Kunchandy etal. 1984;Kunchandy and Kulkarni 1986). A similar profile of potency is found in the present study also.…”
Section: Discussionsupporting
confidence: 92%
“…This discrepancy in action correlates with their potency as well as pharmacokinetic parameters. In in vivo studies, clonidine is reported to be the most potent alpha2 adrenoeeptor agonists even though guanfacine and B-HT 920 are more specific in alphaz receptor binding (Kobinger and Pichler 1980;Scholtysik 1980;Buccafusco et al 1984;Kunchandy et al 1985;Kunchandy and Kulkarni 1986). In in vitro studies, ICI 106270 has been shown to have a specificity and potency equal to clonidine, but it was less potent when administered intravenously, indicating less penetration through the blood-brain barrier due to low lipophilicity.…”
Section: Discussionmentioning
confidence: 97%
“…File neurochemical mechanisms might underlie different components of the withdrawal syndrome. For example, clonidine reversed withdrawal-induced hyperactivity (Kunchandy and Kulkarni 1986), but was ineffective against the anxiogenic response detected in the elevated plus-maze (Baldwin et al 1989).…”
Section: That Differentmentioning
confidence: 98%